Penentuan Beasiswa Pada SMPN 6 Pangkalpinang Menggunakan Metode SAW dan Fuzzy Multi Attribute Decision Making - Fitri Yani; Yuranda Yuranda; Peti Pajarini; Rosmawati Rosmawati (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Scholarship is one of the important tools in advancing education for students either scholarships for outstanding students and underprivileged scholarships. But often the school confused to determine the students who are eligible to receive the scholarship, which in the end the scholarship recipients are not right target .. This is because there is no method or tool used to determine the scholarship recipients. For that purpose, a system is designed to determine the students who are entitled to receive scholarship using Simple Additive Weighting (SAW) method and Fuzzy Multi Attribute Decision Making (FMADM). The SAW method is used to rank from existing alternatives. The FMADM method is used to find alternatives from a number of alternatives with predetermined criteria. The results of this study can be used as a tool in making decisions to recommend an Islamic-based primary school.